2011
DOI: 10.3390/s110100949
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carbonyl Compounds in the Ambient Air of an Industrial City in Korea

Abstract: The purpose of this study was to characterize spatial and temporal variations of carbonyl compounds in Gumi city, where a number of large electronic-industrial complexes are located. Carbonyl samples were collected at five sites in the Gumi area: three industrial, one commercial, and one residential area. Sampling was carried out throughout a year from December 2003 to November 2004. At one industrial site, samples were taken every six days, while those of the other sites were for seven consecutive days in eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The VOC and carbonyl compounds present in malodors have adverse effects on the air quality in the surrounding areas of the sources [ 1 ] as well as on health of the people residing near the sources. The major sources for odorous compounds include agricultural waste, food processing industries [ 2 , 3 ], composting of municipal solid wastes [ 4 ], livestock production industries [ 5 ], semiconductor industries [ 6 ], and the incomplete combustion of hydrocarbon fuels in a range of industries [ 7 ]. The use of ethanol in industries also results in the release of odorous carbonyl compounds into the atmosphere [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The VOC and carbonyl compounds present in malodors have adverse effects on the air quality in the surrounding areas of the sources [ 1 ] as well as on health of the people residing near the sources. The major sources for odorous compounds include agricultural waste, food processing industries [ 2 , 3 ], composting of municipal solid wastes [ 4 ], livestock production industries [ 5 ], semiconductor industries [ 6 ], and the incomplete combustion of hydrocarbon fuels in a range of industries [ 7 ]. The use of ethanol in industries also results in the release of odorous carbonyl compounds into the atmosphere [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The entire fleet of heavy vehicle and more than 50% of the medium-duty vehicles are diesel-driven in Kolkata City. Low C1/C2 ratio also indicates contribution from industrial activities (Seo and Baek, 2011). The C1/C2 ratio was observed to be 1.78 in post-festival season measurement.…”
Section: Entallymentioning
confidence: 92%
“…The carbonyls were extracted with 3 mL of acetonitrile, and then analyzed by HPLC with UV detection at 360 nm (Shimadzu HPLC system, Kyoto, Japan). Details of the carbonyl sampling and analytical methods used in this study can be found elsewhere [ 7 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although questions have been raised from the general public and NGOs in Gumi City regarding the quality of ambient air [ 5 , 7 ], the air quality data that is available for this city has not been adequate to provide accurate information on the real-life situation to policy makers. This is largely because the air quality data available in the city focuses mostly on criteria pollutants, such as particulate matter, sulfur dioxide and nitrogen oxides, whereas little attention has been given to non-criteria pollutants, such as VOCs.…”
Section: Introductionmentioning
confidence: 99%